Regulating Political Parties European Democracies in Comparative Perspective - Napel, H.-M. T. D. ten; Biezen, Ingrid van; Project Muse; Project Muse. (Project Muse, 2016)
The essays that make up Regulating Political Parties were first developed as part of an international symposium at Leiden University focusing on party law. Together, the contributions analyze the regulation of political parties within and beyond Europe from interdisciplinary and comparative perspectives. Addressing both conceptual issues and recent empirical findings, Regulating Political Parties is a valuable examination of an often-overlooked aspect of politics and will be useful for not only scholars, but also legal and political practitioners.
Introduction / Ingrid van Biezen, Hans-Martien ten Napel -- 1. Democracy and the legal regulation of political parties / Richard S. Katz -- 2. Dilemmas of regulating political finance, with special reference to the Dutch case / Ruud Koole -- 3. Lessons from the past : party regulation in the Netherlands / Remco Nehmelman -- 4. The constitutionalization of political parties in post-war Europe / Ingrid van Biezen -- 5. Party laws in comparative perspective / Fernando Casal Bertoa, Daniela R. Piccio, & Ekaterina R. Rashkova -- 6. Explaining legislative conflict over the adoption of political financing law in the European Union / Wojciech Gagatek -- 7. The SGP case : Did it really (re)launch the debate on party regulation in the Netherlands / Hans-Martien ten Napel & Jaco van den Brink -- 8. Will it all end in tears? What really happens when democracies use law to ban political parties / Tim Bale -- 9. Ethnic party regulation in Eastern Europe / Ekaterina R. Rashkova and Maria Spirova -- 10. On the engineerability of political parties : evidence from Mexico / Imke Harbers & Matthew C. Ingram.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Political parties -- Law and legislation -- Europe; Electronic books; Electronic books